Penilaian Kinerja Keuangan dan Tekanan Keuangan Sebelum dan Sesudah Akuisisi (Studi pada Bank KB Bukopin) - Hangdiani, Nadya Talitha (Undergraduate Program in Accounting, Department of Accounting, Faculty of Economics and Business, Universitas Tanjungpura, 2026)
This study aims to compare the financial performance and financial distress condition of PT Bank KB Bukopin Tbk before and after the acquisition by KB Kookmin Bank. Financial performance is measured using financial ratios, namely Return on Assets, Loan to Deposit Ratio, and Capital Adequacy Ratio, while financial distress is measured using the Modified Altman Z-Score model. This research employs a quantitative comparative approach using secondary data obtained from the financial statements of PT Bank KB Bukopin Tbk published on the Indonesia Stock Exchange website during the 2016–2023 period. The sample was selected using purposive sampling, and data were analyzed using the Shapiro-Wilk normality test and paired sample t-test with SPSS version 23. The results show that there is a significant difference in the Loan to Deposit Ratio before and after the acquisition. However, there are no significant differences in Return on Assets, Capital Adequacy Ratio, and Modified Altman Z-Score before and after the acquisition. The findings indicate that the acquisition was followed by improvement in liquidity performance, while profitability, solvency, and financial distress conditions did not show statistically significant changes. Overall, the Loan to Deposit Ratio and Capital Adequacy Ratio are classified as healthy, while Return on Assets is generally classified as unhealthy, although it improved to a healthy level in 2023. The Modified Altman Z-Score shows a gradual improvement after the acquisition, although the difference before and after the acquisition is not statistically significant.